An analysis of Bundesliga matches before and after social distancing by COVID-19 - Santana, H. A. P.; Bettega, O. B.; Dellagrana, R. A. (Science and Medicine in Football, 2021)
Methods: Variables from 305 matches from 2019/2020 Bundesliga season were analyzed. Normality, mean comparisons, analysis of variance and effect sizes were performed. Results: After SD, lower values were observed for goals attempt and distance covered, while higher values were found for passes accuracy and fouls committed (p<0.05). Home teams before SD presented higher number of goals scored at 2nd half and less fouls committed than visiting opponents, after SD away teams had higher number of goals scored at the same half (p=0.043) and a similar number of fouls (p=0.035). Home teams performed more sprints than visiting opponents before SD, but after SD no difference was observed between home and away teams (p=0.042). Total distance covered for both home and away teams were lower after SD (p=0.041). Home teams presented higher values of goal attempts to the target, but changing from small to trivial effects sizes (ES) after SD. However, home advantage was 50.32±19.06% before SD, after SD comeback the home advantage was 40.37±26.08% (ES=0.45). Conclusions: The return to football pitch without stadium supporters, affected some game and physical variables, as well as home advantage.